ANALISIS POTENSI KAWASAN PESISIR PANTAI KOTA PADANG SEBAGAI WISATA OLAHRAGA MARATON BERSKALA INTERNASIONAL - Heru Pramudia (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2019)
Lately, the coastal city of Padang has been improving and being promoted. One of the efforts that can advance tourism is through the introduction and development of national and international sports tourism such as marathons. Marathon is one of the popular sports, such as the New York City Marathon, Parias Marathon, Asia Tokyo Marathon, Tour De France, Bali sailboat competition. This research includes mapping the potential of international scale marathon tourism, how to analyze the potential of sports tourism and the obstacles in the development of sports tourism in the city of Padang. In this study, researchers observed coastal locations that have the potential to develop marathon tourism tourism by looking at the level of tourist development, information on potential locations obtained from informants / informants, these locations have been tested and used for marathon tourism. The internal potential of this marathon sports tour is